Dietary fibre concentrates produced from papaya by-products for agroindustrial waste valorisation - Nieto Calvache, Jhon Edinson (2019)
In this work, papaya agroindustrial wastes were treated with ethanol and subsequently dehydrated to produce pulp or peel dietary fibre concentrates (DFCs). Hot air convection (CV) and microwave (MW) assisted dehydration were studied. The DFCs produced were mainly composed by cell wall polymers such as cellulose, lignin, proteins and non-cellulosic carbohydrates. It was found that convective drying produced DFCs with lower uronic acid content than microwave drying. Besides, pulp DFCs dehydrated by MW presented higher values for hydration properties, compared to those reported in literature. Peel DFCs presented better antioxidant properties than those from the pulp. Use of peel tissue, as well as CV produced DFCs with higher values of glass transition temperature. The characteristics found in the DFCs allow concluding that these products may be added in a diverse range of food products, granting benefits that would normally be obtained using several additives.